The Miocene Depositional Geological Evolution of Phu Khanh, Nam Con Son and Tu Chinh - Vung May Basins in Vietnam Continental Shelf - Dung, Tran Thi; Nghi, Tran; Hung, Nguyen The; Thanh, Dinh Xuan; Ngoc, Pham Bao; Tuyen, Nguyen Thi; Nhan, Tran Thi Thanh; Trang, Nguyen Thi Huyen (VNU Journal of Science: Earth and Environmental Sciences, 2018)
The geological development history of Miocene deposits in three sedimentary basins as Phu Khanh, Nam Con Son and Tu Chinh - Vung May is actually a depositional evolution in relation to sea level change and tectonic movement. The Miocene deposits in three basins were formed in three  cycles corresponding to three depositional sequences: 1/ Early Miocene sequence: In this cycle, the tectonic setting of three basins is similar to one another, the terrain is less differentiated, the environment is mainly alluvial, coastal and shallow marine-bay. Topography of top Miocene surface was strongly deformed by the tectonic events such as compression, fault, fold that had created the rough relief and eroded unconformity surface. The product of erosion processes was supply of terrigenous depositional materials for early Miocene basins under the bay type. 2/ Middle Miocene sequence: The tectonic situation of three basins started changing. The basins were differentiated into 2 parts: The inner shelf with stable geological structure and dominated terrigenous deposits; The outer shelf was stronger subsidence the basin base topography was differentiated with the development of two sediment types: carbonate bearing terrigenous sediments and carbonate reefs. 3/ Late Miocene sequence: in this period the basins were differentiated into two distinct structural zones: the western zone with incline terrain,  the dominated terrigenous sediments and the eastern zone with strong differentiated terrain, reef development they played the erosion zone role and supplied a large amount of biological clastic sediments to the shallow lagoons-bay.